2007
DOI: 10.1038/sj.leu.2404778
|View full text |Cite
|
Sign up to set email alerts
|

MN1 overexpression is an important step in the development of inv(16) AML

Abstract: The gene encoding the transcriptional co-activator MN1 is the target of the reciprocal chromosome translocation (12;22) (p13;q12) in some patients with acute myeloid leukemia (AML). In addition, expression array analysis showed that MN1 was overexpressed in AML specified by inv(16), in some AML overexpressing ecotropic viral integration 1 site (EVI1) and in some AML without karyotypic abnormalities. Here we describe that mice receiving transplants of bone marrow (BM) overexpressing MN1 rapidly developed myelop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
90
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 43 publications
8
90
1
Order By: Relevance
“…On the other hand, we found that 6 of 12 AML samples with high MN1 expression had no detectable HOXA9/MEIS1 expression. The highest MN1 expression level in this group was observed in 2 samples with inv(16) (AML 2 and 6), which has previously been shown to be universally associated with MN1 overexpression (4,6). Analysis of a well-annotated publicly available data set confirmed our results in a larger cohort of patients (30).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…On the other hand, we found that 6 of 12 AML samples with high MN1 expression had no detectable HOXA9/MEIS1 expression. The highest MN1 expression level in this group was observed in 2 samples with inv(16) (AML 2 and 6), which has previously been shown to be universally associated with MN1 overexpression (4,6). Analysis of a well-annotated publicly available data set confirmed our results in a larger cohort of patients (30).…”
Section: Discussionsupporting
confidence: 83%
“…Our data strongly support further evaluation of DOT1L inhibition as a therapeutic strategy for this group of patients. Very high MN1 expression levels are also observed in inv(16) AML, which, in contrast to most other MN1 hi AML, is associated with a good prognosis (4,6). We found sensitivity to DOT1L inhibition in one cell line and 3 patient samples with inv (16).…”
Section: Methodsmentioning
confidence: 58%
See 2 more Smart Citations
“…Retroviral overexpression of human full-length MN1 in a murine model system induces rapid-onset AML. 8,9 We used murine BM cell lines immortalized by retroviral expression of Hoxa9 or NUP98HOXD13, and co-transduced these cells with full-length MN1 or a control vector as described before. 10 Baalc expression was not increased but rather decreased in MN1-expressing NUP98HOXD13 cells as compared with control transduced NUP98HOXD13 cells (Figure 1b).…”
mentioning
confidence: 99%